FEODALISME DALAM NOVEL DRUPADI KARYA SENO GUMIRA AJIDARMA ANALISIS WACANA KRITIS - Khoiriyah, Hidayatul (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
Novel as a work of fiction offers an imaginative world, which is built through various intrinsic and extrinsic elements. This critical discourse analysis of the Drupadi novel by Seno Gumira Ajidarma aims to determine the feudalism discourse the writer adopts through his novel and to determine the author's construction in a developing social context. This research uses critical study as an effort to find; (1) The text structure of Seno Gumira Ajidarma's Drupadi novel, (2) The practice of discourse in Seno Gumira Ajidarma's Drupadi novel, and (3) The form of feudalism in the Drupadi novel by Seno Gumira Ajidarma. The research method used is descriptive narrative with the analysis model of Sara Mills's theory, which focuses on feminists consisting of the subject-object level and the writer-reader level. This research concludes that the structure of the Drupadi novel has a pattern of using a forward plot, namely character recognition, conflict, climax, anticlimax, and ending. This plot is often used in other narrative texts, so, it can be concluded that the structure of the text in the Drupadi novel by Seno Gumira Ajidarma includes; character introduction, conflict, climax, anticlimax, end / koda. In addition, Drupadi's novel shows the discourse of feudalism through the subject-object level and the writer-reader level. These results were obtained from the analysis of feudalism practices found in the novel Drupadi. These are the beliefs, beliefs, views, and ultimately the ideological vision that is represented by Seno Gumira Ajidarma's Drupadi novel in his discourse. Like postmodernist thoughts, the ideology that is represented must fight, challenge, and criticize the ideology that is currently in power to become a dominant discourse. Seno Gumira Ajidarma's ideology combines with the ideology of the spirit of the postmodern era.